Gene expression profiling of liver from dairy cows treated intra-mammary with lipopolysaccharide - Vels Lotte; Røntved Christine; Sørensen Peter; Jiang Li; Ingvartsen Klaus L (BMC Genomics, 2008)
Abstract Background Liver plays a profound role in the acute phase response (APR) observed in the early phase of acute bovine mastitis caused by Escherichia coli (E. coli). To gain an insight into the genes and pathways involved in hepatic APR of dairy cows we performed a global gene expression analysis of liver tissue sampled at different time points before and after intra-mammary (IM) exposure to E. coli lipopolysaccharide (LPS) treatment. Results Approximately 20% target transcripts were differentially expressed and eight co-expression clusters were identified. Each cluster had a unique time-dependent expression profile and consisted of genes involved in different biological processes. Our findings suggest that APR in the liver is triggered by the activation of signaling pathways that are involved with common and hepatic-specific transcription factors and pro-inflammatory cytokines. These mediators in turn stimulated or repressed the expression of genes encoding acute phase proteins (APP), collectins, complement components, chemokines, cell adhesion molecules and key metabolic enzymes during the APR. Hormones, anti-inflammatory and other hypothalamus-pituitary-adrenal axis (HPAA) linked mediators also seemed to participate in APR. Conclusion Performing global gene expression analysis on liver tissue from IM LPS treated cows verified that the liver plays a major role in the APR of E. coli mastitis, and that the bovine hepatic APR follows the same pattern as other mammals when they are challenged with LPS. Our work presents the first insight into the dynamic changes in gene expression in the liver that influences the induction, kinetics and clinical outcome of the APR in dairy cows.